Philosophy and philosophers : an introduction to western philosophy - Shand, John, 1956- (UCL Press, 1993)
This introduction to the major philosophers and schools is philosopher based rather than topic based. The book discusses figures from the pre-Socratics to the 20th century and includes an up-to-date bibliography to advise readers on what to expect.